Influence of biological control agents Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV) on intensity of the attack twig caterpillar (Ectropis bhurmitra Wlk) and yield of tea plant (Camellia sinensis (L.) O. Kuntze) clone GMB 7 - Merry Antralina; Joko Santoso (Research Institute for Tea and Cinchona, 2015)
The objective of this research was to evaluate the effect of Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV) on attack intensity of twig caterpillar (Ectropis bhurmitra Wlk) and the yield of clone Gambung 7 tea plant. The research was conducted at the Research Institute for Tea and Cinchona, Gambung, Bandung, from May 2011 till June 2011. AÂ randomized block design was used with five treatments and replicated four replications. Application of five controls method for the twig caterpillar were performed. HaNPV at Â 4 x 106 PIB/mI, and 4 x 104 PIB/ml, Bacillus turingiensis (Thuricide) 1 g/L, Spinosad (Tracer 120 SC) 0,5 ml/L, and chemical insecticides (Electric 500 EC) 0,5 ml/L. The results indicated that HaNPV at both the density gave the same effect compare to other insecticides tested on the attack intensity of twig caterpillar as well as yield of tea plant clone Gambung 7.